PENGEMBANGAN MEDIA DASI (DIORAMA SIKLUS AIR) UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V SD - Yanti, Yulia Eka; Huda, Miftahul (Universitas Islam Raden Rahmat Malang, 2023)
This study aims to develop a learning media product named DASI (Water Cycle Diorama) so that fifth grade students' understanding of the concept of the water cycle theme 8 sub-theme 1 learning 2. The type of research used is Research and Development (R&D) research. The R&D model used is the 4D model (Thiagarajan). Data collection uses the necessary research instruments including: interviews, concept understanding tests, questionnaires, and documentation. The results showed that 1) the DASI media (Water Cycle Diorama) was declared suitable for use based on the validation results of media experts obtaining a final percentage of 100% with valid qualifications and the validation results of material experts obtaining a final percentage of 86% with valid qualifications. While the student response questionnaire obtained a final percentage of 89% with very decent qualifications and 88% with very decent qualifications for the large group. 2) the DASI learning media (Water Cycle Diorama) was declared effective for increasing students' understanding of concepts based on the average score of the small group pretest of 54 and the average score of the posttest of 76 while the classical pretest mastery was 40% and the classical was 80% with increased results learning by 40%. While the average score of the small group pretest was 48 and the posttest average score was 74.5 while the classical pretest completeness was 15% and the posttest classical completeness was 75% with an increase in learning outcomes by 60%.